2013
DOI: 10.1371/journal.pone.0071048
|View full text |Cite
|
Sign up to set email alerts
|

Expression of COX-2, CD44v6 and CD147 and Relationship with Invasion and Lymph Node Metastasis in Hypopharyngeal Squamous Cell Carcinoma

Abstract: To assess the expression of COX-2,CD44v6 and CD147 in hypopharyngeal squamous cell carcinomas and the three biomarkers correlation with tumor invasion and lymph node metastasis of Chinese people. 101 cases of surgically excised primary tumor were included in this study, and 40 tissues of epithelium adjacent to carcinoma were used as controls. We characterized the immunohistochemical expression of COX-2, CD44v6, and CD147 in141 formalin-fixed, paraffin-embedded tissues, and measured the mean optical density (OD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
4
31
0
1
Order By: Relevance
“…This shows that EMMPRIN protein expression is closely associated with LNM. The result corresponds well with the previously reported literature ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
“…This shows that EMMPRIN protein expression is closely associated with LNM. The result corresponds well with the previously reported literature ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
“…9 studies were excluded as they did not provide sufficient data for extracting odds ratio (OR) or hazard ratio (HR) or 95% confidence intervals (CI) [2836], leaving 29 studies that fulfilled the eligibility criteria [2227, 3759] (Table 1). Four studies reported no site-specific HNC [24, 5457] and others recorded site-specific HNC. There were 7, 6 and 9 studies focused on oral cancer (OC) [22, 25, 27, 3740], laryngeal cancer (LC) [4146] and nasopharyngeal cancer (NPC) [23, 26, 4753], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis has revealed that the expression of CD147 is an independent prognostic indicator for patients with HCC and non-small cell lung cancer [ 58 , 136 ]. In addition, low CD147 expression has also been suggested as a significantly favorable prognostic factor in gastric carcinoma [ 137 ], glioblastoma [ 138 ], endometrial cancer [ 139 ], and hypopharyngeal squamous cell carcinoma [ 140 ]. In patients with urothelial carcinoma of the bladder (UCB), univariate analysis revealed that high MCT1 and CD147 expressions were correlated with poor overall survival, whereas high MCT4 expression was associated with poor recurrence-free survival.…”
Section: Therapeutic Potential Of Cd147 and Mcts In Tumorsmentioning
confidence: 99%